The preparation of Dermatophilus congolensis antigen and its testing by means of immunodiffusion test and electrophoresis - Djaenudin Gholib; Subiyanto . (Indonesian Center for Animal Research and Development (ICARD), 1998)
The filtrate antigen ofDermatophilus congolensis was prepared based on the Makinde method, whereas the whole cell antigen was based on the Bida and Kelley method. Filtrate antigen of Dermatophilus congolensis has been tested with positive serum from experimental animals, guinea pigs and sheep by means of immurrodiffitsion test and electrophoresis . Positive serum was produced by inoculation of whole cell antigen of D. congolensis to the animals . The results showed that the immunodiffusion test resulted in one and two precipitation lines with positive serum of sheep and guinea pigs respectively. Electrophoresis SDS-PAGE presented about 8 bands with molecular weight in the range from above 30 kD to more than 94 kD. The bands were then transferred into nitrocellulose membrane and gave positive reaction with positive serum from sheep. Key words : Antigen, Dermatophilus congolensis, immunodiffusion, electrophoresis